CONSUMER ACCEPTANCE OF SEAWEED BALL (Eucheuma cottonii) FORTIFIED WITH CATFISH PROTEIN CONCENTRATE (Pangasius hypophthalmus) - Naibaho, Marianche F; ', Dewita; ', Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The study was conducted to evaluate consumer acceptance of seaweed ball fortified with catfish protein concentrate . About 5 kg seaweed was taken from a fish market in Pekanbaru. Three types of seaweed balls were prepared from seaweed flour which was fortificated respectively with 5%, 10%, and 15% catfish protein concentrate. The seaweed balls were evaluated for consumer acceptance and chemical composition. The results indicate that the seaweed balls added with 15% catfish protein concentrate was the most preferable by consumers. The seaweed ball contains water 58%, protein 12,85%, and crude fiber 5,23%.